Efektivitas Penggunaan Mobile Payment Online System (MPOS) Pada Pemungutan Pajak Restoran Di Kabupaten Mempawah (Studi Kasus Pada Badan Pengelola Pajak dan Retribusi Daerah Kabupaten Mempawah) - Ihsan, Ahmad (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2025)
This study evaluates the effectiveness of the Mobile Payment Online System (MPOS) in supporting restaurant tax collection in Mempawah Regency. The study employs a descriptive qualitative approach and was conducted at the Regional Tax and Retribution Management Agency of Mempawah Regency and selected restaurant taxpayers. Data were collected through interviews, observation, and document analysis involving tax officials and MPOS users. Effectiveness was assessed based on policy accuracy, implementation accuracy, target accuracy, ease of use, and the ability to address operational constraints. The results show that restaurant tax collection after the implementation of MPOS was categorized as highly effective, with effectiveness ratios of 123% in 2019, 119% in 2020, and 120% in 2021. MPOS facilitates online transaction reporting, enables real-time monitoring by tax officials, and helps reduce underreporting and other forms of taxpayer non-compliance. The system is also considered easy to learn and operate. Although several constraints were identified, including unstable internet connections, device malfunctions, limited personnel, and taxpayer reluctance to record transactions, these problems were generally resolved through technical assistance, vendor support, and internet access provision. Overall, MPOS improves the transparency, monitoring, and effectiveness of restaurant tax collection in Mempawah Regency.